LANGUAGE ACQUISITION IN PREWRITING, DRAFTING, REVISING, EDITING AND PUBLISHING - Zalzulifa Zalzulifa; Liza Amalia Putri (Politeknik Negeri Media Kreatif, 2022)
This research is back-worded by the pragmatic experiential learning problems theresearcher faces in daily routine activities of teaching learning from first to fourthsemester (2008-2021) at PoliMedia. It has accumulated into the researcher’s pragmaticfindings that teaching English for publishing students with its basic skills (reading,writing, listening, speaking) should be in line with the needed basic competencies oflanguage assessment in the publishing needed skills (pre-writing, drafting, revising,editing, and publishing). However, in order to assure the pragmatic findings it isneeded to do the academic analysis through the following academic researchmethodology, including: setting and time, research design, population and sample,data collection instrument, and data analysis. The research uses qualitative approachthrough seeing, observing, discussing and studying some related documents takenfrom questioannaire, interview, simulation and focus group discussion amonglecturers.. The data shows various level of language acquisition (reading, writing,listening, speaking) found in prewriting, drafting, revising, editing and publishing. While there are seventeen students’ needed technical skills to be supported in learningprocess, such as: 1). team working skills; 2) oral communication skills; 3) problemsolving skills, 4) customer handling skills, 5) management skills, 6) general IT userskills, 7) technical and practical skills, 8) office administration skills, 9) writtencommunication skills, 10) literacy skills, 11) numeracy skills, 12) IT professional skills,13) foreign language skills, 14) grappling with grammar skill, 15) speed reading skills,16) note-taking skills and 17) negotiating skills.